Between distance and inheritance: A study of the relation between Malaysian Chinese literature and modern Chinese literature - Fan, P.W. (2010)
Besides mainland China, Taiwan and Hong Kong, Chinese literature is most developed in Malaysia. Before 1945, Chinese literature had a major influence on Malaysian literature in Chinese (Mahua literature), from the backgrounds to the thoughts of the literary works. It became a major tributary of overseas Chinese literature. After the 2nd World War, publications in China were prohibited from entering Malaysia; therefore, Malaysian Chinese lost connection with the literary works from China for 45 years. Malaysian Chinese had to turn to Hong Kong and Taiwan for their search for Chinese literature. However, teaching materials in Malaysia secondary textbooks continued to be based on the ``May Fourth Literature'' works, which exerted a deep influence on the literature lovers in Malaysia, both in their thoughts and writing skills. This article discusses the dissemination of modern Chinese literature in Malaysia and the relationship between Malaysian Chinese Literature and modern Chinese Literature.